2018
DOI: 10.33102/jmifr.v15i2.177
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Organizational Commitment Between Islamic Human Resource Practices and Organizational Performance Among Islamic Banks of Bangladesh

Abstract: This paper aims at exploring the impact of Islamic human resource (HR) practices on organizational performance though organizational commitment. Data were collected from randomly selected 170 branch managers of six Islamic Banks listed on Dhaka Stock Exchange of Bangladesh. After collecting data, descriptive analysis and structural equation model were done to examine reliability and validity of the model. By analysis, the study finds that Islamic HR practices have more significant impact on organizational perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 45 publications
0
28
0
3
Order By: Relevance
“…With the help of this structural equation model technique, it was identified that the most of the Islamic practices of HR has significant effects on the organizational performance. Further it suggests that the Islamic Banks have to work on the Islamic HR practices to maintain their performance in the organizations (B. K. Dhar et al, 2018). Further the study suggests that the managers of organizations have to provide great focus on the training and development side of the organization keeping is view the Islamic principles as these principles improves the relationship between these variables which is evident from the results.…”
Section: Recommendations and Conclusionmentioning
confidence: 71%
See 1 more Smart Citation
“…With the help of this structural equation model technique, it was identified that the most of the Islamic practices of HR has significant effects on the organizational performance. Further it suggests that the Islamic Banks have to work on the Islamic HR practices to maintain their performance in the organizations (B. K. Dhar et al, 2018). Further the study suggests that the managers of organizations have to provide great focus on the training and development side of the organization keeping is view the Islamic principles as these principles improves the relationship between these variables which is evident from the results.…”
Section: Recommendations and Conclusionmentioning
confidence: 71%
“…It was found by them that IHRM has positive impact on the organizational justice and commitment of employees. B. K. Dhar et al, (2018) explored the effects of IHRM practices with organizational commitment on the performance of six different Islamic listed banks. The analysis showed that, with organizational commitment, the practices of Islamic HR have higher significant effect on the performance of organizations rather than the having direct impact of Islamic practices of HR on the organizational performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, the third stream of researchers wanted to portray the nature and extent of HCD. Though Abeysekera and Guthrie (2004) observed three streams of research on HCD but another stream of research, maybe the fourth stream, to explore the views of several stakeholders regarding HCD had also been conducted (see, for example, Abeysekera, 2008; Absar, 2016; Chowdhury & Dhar, 2012; Dhar & Mohammed, 2015; Dhar et al, 2017; Huang et al, 2013; Masruki, Khairulannuar, & Dhar, 2020; Masruki, Samsudin, & Dhar, 2020; Murthy & Abeysekera, 2007).…”
Section: Hcd Literature Reviewmentioning
confidence: 99%
“…The long‐run economic growth of a country depends on the functioning of financial markets. The banking industry in Bangladesh plays a major role in the economic development of the country (Dhar, 2019a, 2019b; Dhar et al, 2018). Bangladesh's Banking sector contributed 3.39% of the GDP by the sector in FY 2020, and 3.42% in FY 2019, which is the highest level of sectoral contribution in Bangladesh's history (thefinancialexpress.com, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the financial performance of a company is basically evaluating the impact of the strategies of a firm regarding financial matters. The results of such decisions are evident in the evaluation of the worth of a company or a business enterprise through assessment of the return on investment and return on assets (Dhar, 2019a,b;Dhar et al, 2017Dhar et al, , 2018Saeed et al, 2017;Rouhoma et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%